Global optimization and the energy landscapes of Dzugutov clusters - Doye, J; Wales, D; Simdyankin, S (2001)
The global minima of clusters bound by a Dzugutov potential form non-compact polytetrahedral clusters mainly composed of interpenetrating and face-sharing 13-atom icosahedra. As the size increases, these icosahedral units first form linear arrays, then two-dimensional rings, then three-dimensional networks. Characterization of the energy landscapes of these clusters shows that they are particularly rough and generally exhibit a multiple-funnel topography. These results provide new insights into the structure and dynamics of bulk supercooled Dzugutov liquids and the form of the bulk phase diagram.